2020
DOI: 10.1371/journal.pone.0237400
|View full text |Cite
|
Sign up to set email alerts
|

Whole-blood transcriptome profiling reveals signatures of metformin and its therapeutic response

Abstract: Metformin, a biguanide agent, is the first-line treatment for type 2 diabetes mellitus due to its glucose-lowering effect. Despite its wide application in the treatment of multiple health conditions, the glycemic response to metformin is highly variable, emphasizing the need for reliable biomarkers. We chose the RNA-Seq-based comparative transcriptomics approach to evaluate the systemic effect of metformin and highlight potential predictive biomarkers of metformin response in drug-naïve volunteers with type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…10,11). It has been shown that metformin exerts its effects on the microbiome already in the first 24 hours ( 10 )⁠ and that the alterations in the gut microbiome could be related to the metformin-induced immune response ( 13 )⁠.…”
Section: Introductionmentioning
confidence: 99%
“…10,11). It has been shown that metformin exerts its effects on the microbiome already in the first 24 hours ( 10 )⁠ and that the alterations in the gut microbiome could be related to the metformin-induced immune response ( 13 )⁠.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that the observed transcriptomic changes are a faithful representation of the DCS state, care was taken to minimize interindividual differences amongst the divers selected for this study. The peripheral blood transcriptome is known to broadly reflect the combined effects of pharmacotherapy, chronic disease, and environmental exposures such as smoking ( Lampe et al, 2004 ; Liu Y. et al, 2015 ; Beretta et al, 2020 ; Ustinova et al, 2020 ). While these factors are integral components of many human studies, they can cause confounding in gene expression experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the transcriptome finds great application in studies aimed at searching for new molecular markers and therapeutic targets. They involve numerous human diseases, including neurological disorders such as chronic pain [19], multiple sclerosis [20], diabetes [21], cardiovascular disease [22], cancers, and their response to treatment [23]. Microarrays and high-throughput RNA sequencing are of great importance, as they rapidly provide a huge amount of data on the processes or organisms under study [24].…”
Section: Multiomics Strategiesmentioning
confidence: 99%